Identification of a 52 kb deletion downstream of the SOST gene in patients with van Buchem disease. Issue 2 (1st February 2002) - Balemans, W; Patel, N; Ebeling, M; Van Hul, E; Wuyts, W; Lacza, C; Dioszegi, M; Dikkers, F G; Hildering, P; Willems, P J; Verheij, J B G M; Lindpaintner, K; et al.
Abstract : Van Buchem disease is an autosomal recessive skeletal dysplasia characterised by generalised bone overgrowth, predominantly in the skull and mandible. Clinical complications including facial nerve palsy, optic atrophy, and impaired hearing occur in most patients. These features are very similar to those of sclerosteosis and the two conditions are only differentiated by the hand malformations and the tall stature appearing in sclerosteosis. Using an extended Dutch inbred van Buchem family and two inbred sclerosteosis families, we mapped both disease genes to the same region on chromosome 17q12-q21, supporting the hypothesis that van Buchem disease and sclerosteosis are caused by mutations in the same gene. In a previous study, we positionally cloned a novel gene, called SOST, from the linkage interval and identified three different, homozygous mutations in the SOST gene in sclerosteosis patients leading to loss of function of the underlying protein. The present study focuses on the identification of a 52 kb deletion in all patients from the van Buchem family. The deletion, which results from a homologous recombination between Alu sequences, starts approximately 35 kb downstream of the SOST gene. Since no evidence was found for the presence of a gene within the deleted region, we hypothesise that the presence of the deletion leads to a down regulation of the transcription of the SOST gene by a cis regulatory action or a position effect.